Controlled Delivery of Amoxicillin and Rifampicin by Three-Dimensional Polyvinyl alcohol/Bismuth Ferrite Scaffolds - Ilgar, Sule; Ulag, Songul; Sahin, Ali; Gunduz, Oguzhan; Ustundag, Cem Bulent (WILEY-V C H VERLAG GMBH, 2023)
Skin is a protective barrier that can protect against environmental influences and renew itself. However, in some cases, this regenerative property is lost, and this causes delays in wound healing. Wound healing is a complex and long-lasting phase. Any bacterial infection during the wound healing process delays wound healing. The therapeutic efficacy can be increased by using nanocarrier drug delivery systems to the target tissue with modern wound dressings. Controlled nano drug delivery systems increase the therapeutic efficacy in the treatment of diseases and provide a faster recovery process. In this study, amoxicillin (AMX) and rifampicin (RIF) were loaded into the bismuth ferrite (BFO) particles which were synthesized with the co-precipitation method. Then, these drug-loaded BFO particles (0.075 %) were added separately to 13 % polyvinyl alcohol (PVA) solution and the solutions were printed three-dimensionally to obtain three dimensional scaffolds. With these designed scaffolds, it is aimed to reduce the risk of inflammation in wound tissues and increase therapeutic efficacy with controlled release. The SEM images proved that homogeneous pore distributions could be achieved with these combinations. The tensile test results showed that drug-loaded BFO addition increased the mechanical strength of the 13 % PVA scaffold. The biocompatibility test results demonstrated that the highest viability values of the human adipose tissue-derived mesenchymal stem cells were obtained for AMX-added 13 % PVA scaffolds.
Keywords: Bismuth ferrite; controlled drug delivery; polyvinyl alcohol; 3D printing; wound dressing; DRUG-DELIVERY; NANOPARTICLES; HYDROGELS; TISSUE; PVA; NANOCOMPOSITE; Chemistry